Ethno-Cultural Conflict in Sri Lanka: A Case Study - LAMBERT, GLENROY; PASCUAL-LAMBERT, NELEN (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Since its independence, Sri Lanka has seen an escalating ethno-cultural conflict between the Buddhist Sinhalese. the most populous ethnic group,and the Hindu Tamils, the largest ethnic minority It, therefore, presents a classic example of a nation deeply divided by cleavages of ethnic heritage,religious affiliation, language, and habitat. In light of these assumptions and realities, the paper examines the cultural dimension of Tamil separatism and theorizes that the separatist movement is animated not only by concerns about Tamil prospects in the Sinhala-dominated state of Sri Lanka but also by the profound pride that Tamils take in their cultural tradition. Sri Lankan Tamil separatism, however also raises the specter that conservative Jaffa Vellalars might dominate an independent Tamil state. Thus, reform-minded Sri Lankan Tamils must consider such implications against the ominous trends towards violence and geographic polarization of Sri Lanka's two conflicting ethnic Communities.